2019
DOI: 10.1186/s13063-019-3364-x
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a randomised controlled trial to evaluate the effectiveness of improving tuberculosis patients’ treatment adherence via electronic monitors and an app versus usual care in Tibet

Abstract: Background Treatment non-adherence is a serious challenge to effective tuberculosis (TB) control in Tibet. In this study we will pilot and evaluate the effectiveness of using new electronic monitors (e-monitors) and a smartphone app to improve treatment adherence among new pulmonary TB patients in Tibet. Methods We will use a multicentre, parallel-group, individually randomised controlled, superiority trial with blinded outcome evaluation and unblinded treatment. We wil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 31 publications
0
29
0
1
Order By: Relevance
“…However, many studies have emphasized the importance of exploring the use of innovative electronic health (e-health) technology in disease case management to improve patient adherence and treatment outcomes. 36,[38][39][40][41][42] Some studies found it was easier to monitor adverse events and non-adherent behavior through mobile phone messaging, and one study in China found that using an electronic medication monitor (EMM) which provides regular reminders to take medication reduced poor-adherence behaviors. E-health management may be a more preferred management method 42 and should be integrated into future MTCM delivery systems.…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies have emphasized the importance of exploring the use of innovative electronic health (e-health) technology in disease case management to improve patient adherence and treatment outcomes. 36,[38][39][40][41][42] Some studies found it was easier to monitor adverse events and non-adherent behavior through mobile phone messaging, and one study in China found that using an electronic medication monitor (EMM) which provides regular reminders to take medication reduced poor-adherence behaviors. E-health management may be a more preferred management method 42 and should be integrated into future MTCM delivery systems.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a global consensus that TB patients' medicationtaking behavior must be managed. Therefore, in addition to strengthening patient knowledge of PTB treatment, on the one hand, the self-management capability of PTB patients must be strengthened; on the other hand, because DOT is difficult to implement in Tibet and has disadvantages, 7,26 it is necessary to find feasible alternative strategies to DOT, such as video-observed treatment, wirelessly observed therapy, short message service reminders and medication reminders, [27][28][29][30] to improve medication adherence among PTB patients in Tibet.…”
Section: Discussionmentioning
confidence: 99%
“…5 The national TB survey reported that 25.3% of TB patients missed more than one dose of anti-TB drugs. 6 In Shigatse, a city in the Tibet Autonomous Region, the rate of default from TB treatment was 28% in 2016, 7 which was higher than the WHO recommendation of less than 10%. 8 Medication nonadherence has been an important driver of TB drug resistance in Tibet and has resulted in treatment failure, disease relapse, prolonged infection, and even death.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This app has previously been effectively used in mass public health education programmes [27,28]. In Tibet, we have employed the WeChat app to link with electronic medical records (EMR) and monitoring boxes to support tuberculosis patients in completing their treatment under harsh travel conditions [29].…”
mentioning
confidence: 99%